Implementation of Policing in Violent Crimes Against Children with Special Needs: (Case Study: Sexual Abuse of Children with Disabilities within the Jurisdiction of Polresta Serang Kota) - David Adhi Kusuma (Asosiasi Dosen Muda Indonesia, 2026)
Violence against children with disabilities remains one of the most complex human rights and criminal justice issues in contemporary society. Children with special needs are positioned as highly vulnerable groups due to communication limitations, social dependency, psychological vulnerability, discrimination, and limited access to legal protection mechanisms. This article analyzes the implementation of policing strategies in handling violent crimes against children with disabilities, particularly sexual abuse cases within the jurisdiction of Polresta Serang Kota. The study aims to examine police responses, investigative procedures, institutional barriers, victim protection mechanisms, and legal implementation regarding child victims with disabilities. The study employs a qualitative research method using a case study approach. Data were collected through literature review, legal document analysis, media reports, scientific journals, previous empirical studies, and comparative legal analysis. The research applies thematic qualitative analysis to identify patterns related to policing practices, victim-centered justice, accessibility of legal systems, and institutional effectiveness.